Comparing Eyesi Virtual Reality Simulator and Traditional Teaching Methods for Direct Ophthalmoscopy: Students' Perspectives at Indiana University School of Medicine - Tso, Hanna L.; Young, Jason; Yung, C. W. (Journal of Academic Ophthalmology, 2021)
Background The fundus examination is an essential part of any ophthalmologic evaluation. However, medical students and primary care physicians often lack confidence with direct ophthalmoscopy. Virtual reality simulators are being employed in medical education to teach this technically challenging examination.Objective To compare medical student ratings of the Eyesi Direct Ophthalmoscope Simulator and traditional small group teaching methods for learning direct ophthalmoscopy skills.Methods All medical students at Indiana University School of Medicine traditionally learn direct ophthalmoscopy in their first 2 years during a small group session led by a physician instructor. Students who later enrolled in ophthalmology clinical electives during 2019 and 2020 were invited to additionally complete the Eyesi Direct Ophthalmoscope Simulator virtual reality curriculum. A voluntary, anonymous survey was sent between June and August 2020 to students who had completed both the traditional and Eyesi simulator sessions. Students were asked to rate their confidence in performing direct ophthalmoscopy following each session, and to indicate which teaching method was superior and why. Chi-square analysis was used to compare categorical variables.Results Students' confidence ratings for performing direct ophthalmoscopy were significantly higher following completion of the Eyesi simulator session compared with the traditional small group session (p < 0.001). Four-fifths of respondents felt that the Eyesi simulator was superior to the traditional small group for learning the skills of direct ophthalmoscopy, while one-fifth felt that the two sessions were equally effective (p < 0.001). None of the students responded that the small group session was the superior teaching method.Conclusion The Eyesi Direct Ophthalmoscope Simulator was rated highly among medical students and offers distinct learning advantages that could not be replicated in a traditional small group environment, such as providing numerous examples of pathological findings and allowing unlimited examination time without concern for patient's inconvenience or light exposure. The Eyesi simulator is a promising tool for teaching direct ophthalmoscopy to medical students. Ultimately, familiarity with the fundus examination will enable future physicians across specialties to better evaluate and appropriately refer patients with ocular fundus pathology.
Keywords: medical education; direct ophthalmoscopy; Eyesi; virtual reality simulator